2018
DOI: 10.1016/j.jtcvs.2018.03.152
|View full text |Cite
|
Sign up to set email alerts
|

Radiotracer localization of nonpalpable pulmonary nodules: A single-center experience

Abstract: Radiotracer localization is a simple and effective technique for intraoperative identification of small pulmonary nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…tumor border to the nearest visceral pleura as the tumor depth, with a nodule with a depth of ≥20 mm considered as deep (18). Several studies have reported that localization of a nodule with a depth of approximately 20-25 mm could be feasible and effective (9,(18)(19)(20). Nodules with a depth of >3 mm are usually considered deep and an anticipated lobectomy was required (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tumor border to the nearest visceral pleura as the tumor depth, with a nodule with a depth of ≥20 mm considered as deep (18). Several studies have reported that localization of a nodule with a depth of approximately 20-25 mm could be feasible and effective (9,(18)(19)(20). Nodules with a depth of >3 mm are usually considered deep and an anticipated lobectomy was required (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, methylene blue has certain limitations; it can easily diffuse over the pleural surface, rendering it difficult to identify alongside extensive anthracotic pleural pigments. Moreover, methylene blue does not mark the depth of a lesion (19). Lin et al were the first to report using of PBV dye instead of methylene blue for localization (14), with a high success rate and safety.…”
Section: Management Of a Deep-situated Pulmonary Nodule Is Challenginmentioning
confidence: 99%
“…Gamma-emitting radioisotopes (99mTc) attached to large albumin molecules can be used for localization under CT guidance (28)(29)(30). On the day of the operation, 0.2 mL of 99mTc-labeled human serum albumin microspheres is injected as close to the lesion as possible through the thoracic wall with a 22-gauge needle under local anesthesia (30). Some centers add 0.1-0.2 mL of nonionic contrast to the radiotracer to confirm the presence of radiotracer within the nodule on post-procedure CT scans (28,31).…”
Section: Localization With Radiotracersmentioning
confidence: 99%
“…Such markers are therefore intensively explored for preoperative and intraoperative target localization and navigation. Examples of currently available markers for surgical guidance include hook wires, iodinated oils (Lipiodol) and 99m Tc-labeled nanoparticles that are visible in ultrasonography, CT or SPECT imaging, respectively [3][4][5]. Marker-associated complications are however common, e.g.…”
Section: Introductionmentioning
confidence: 99%